Impact of stringent interpretation of tax provisions on funded research in universities: A case study from Sri Lanka - Nanayakkara, P.K.M.; Kamardeen, N.; Pathirana, D. (University of Colombo, 2025)
One of the basic principles of income tax is that only income, and not savings, should be taxed. The progressive violation of this principle has resulted in many non-income receipts being taxed under the Sri Lankan tax system. Previously, income earned by providing services to foreign clients, whether the services were performed within or outside Sri Lanka, was entirely exempt from income tax, provided the earnings were brought into the country. However, from April 1, 2025, such income was subject to a maximum tax rate of 15%, provided it was received in foreign currency and remitted to Sri Lanka through a licensed bank. If the income is not remitted via the formal banking system, it will be taxed according to the standard progressive income tax rates, which may reach up to 36%, depending on the individual’s total taxable income. The particular case study at hand concerns the reimbursement of the cost of an air ticket purchased by a foreign collaborator of a research project led by a Sri Lankan public university. The Inland Revenue Department of Sri Lanka withheld 14% of the total cost of the ticket as income tax. This deduction led to the recipient, who is not a taxpayer resident in Sri Lanka, receiving only 85% of the reimbursable amount...
Keywords: Tax deductions; Non-resident citizens; Foreign source income; Non-income receipts; Negative list